Laboratory manual and workbook in general biology (Quezon City : C & E Publishing, 2012)
This is a comprehensive edition of a combined laboratory manual and workbook in general biology. It covers a number of activities from the cellular to the organismic levels of life, and to an awareness of the community. The clear, faculty- and student-friendly, and straightforward discussions and exercises are aimed at developing the critical thinking and research potential of students.
Keywords: Biology--Laboratory manuals; Biology--Experiments.